Autobiografia Docente: (Des)caminhos Pedagógicos - Batista, Madson Moura (2020)
In 1990 I started my professional life in public education. The objective of this dissertation is, at first, to scan, systematize and select the most relevant of my journey as a teacher at school, offering an account of this formative and professional tra